Empyema in a Woman with Cystic Fibrosis: A Cautionary Tale. (5th March 2013) - Coates, Anne; Schaefer, Oren; Uy, Karl; O'Sullivan, Brian P.
Abstract : Cystic fibrosis (CF) is a disease which predisposes individuals to recurrent infective exacerbations of suppurative lung disease; however, empyema is a rare complication in these patients. Empyemas secondary to Staphylococcus aureus and Burkholderia cepacia have been described in patients with CF. We report the case of pleural empyema with mixed S. aureus and Pseudomonas aeruginosa infection in a 34-year-old woman with CF, which was managed with ultrasound-guided pigtail catheter insertion, fibrinolysis, and antibiotic therapy. Physicians should be aware of this unusual complication in CF patients, especially those receiving an immunosuppressive therapy.